Modelagem numérica de pilares curtos de concreto confinados com PRFC solicitados por força de compressão concêntrica e excêntrica - Santos, Matheus de Santana (2022)
The use of Carbon Fiber Reinforced Polymers (CFRP) in the strengthening and repair of reinforced concrete structures dates back approximately three decades. Among the factors that have consolidated the application of this material in civil construction are its excellent mechanical properties, its low specific weight, and its high resistance to corrosion. Currently, CFRP has been widely applied to reinforce columns of buildings, bridges, and viaducts as a way to increase the strength and deformation capacity of these structures. The research developed in this paper aimed to perform the numerical modeling of columns subject to concentric and eccentric loading reinforced with CFRP, through the Finite Element Method (FEM), using the commercial software ABAQUS. The reinforcement technique with CFRP externally bonded to the concrete surface, known as External Bonded (EB), was addressed. The simulations were developed considering the physical nonlinearity of concrete, through the constitutive model named Concrete Damaged Plasticity (CDP), and the physical nonlinearity of reinforcement. The numerical models were validated using experimental samples taken from the works of Carrazedo (2005) and Maaddawy et al. (2010), whose numerical results showed good compatibility in terms of force and displacement. The efficiency of the CFRP reinforcement was proven even with the presence of eccentricity. However, the average gain in strength capacity and ductility under eccentric loading was higher for the lower eccentricity level. In addition, a parametric analysis was performed to evaluate the influence of column cross-section shape on the effectiveness of CFRP confinement for models tested under various eccentric load conditions. Based on these results, it was found that the data obtained did not express a consistent trend under the effect of cross-section shape on load gain, but demonstrated that increasing eccentricity decreases strength and improves displacement capacity.